Rekomendasi Game Edukasi dengan Mengunakan Metode ItemBased Collaborative Filtering - Harahap, Andrian Rajab; Dafitri, Haida; Chiuloto, Kalvin (Forum Kerjasama Pendidikan Tinggi, 2026)
In the digital era, choosing the right educational game is a challenge for parents, so a recommendation system is needed that is able to provide relevant suggestions according to children's needs. This research aims to build an educational game recommendation system using the Item-Based Collaborative Filtering method. This method works by analyzing user rating patterns for games, then calculating the level of similarity between games using the Adjusted Cosine Similarity and Weighted Sum algorithms to produce personalized recommendations. Data is obtained explicitly through user interaction in the form of likes and comments on available games. System testing was carried out involving 22 respondents. To the question